1990
DOI: 10.1139/z90-270
|View full text |Cite
|
Sign up to set email alerts
|

A comparative survey of imposex in northeast Pacific neogastropods (Prosobranchia) related to tributyltin contamination, and choice of a suitable bioindicator

Abstract: Imposex, the manifestation of male morphological sex characters in females of functionally dioecious neogastropod taxa, is an abnormal response to tri-n-butyltin (TBT) contamination introduced to the marine environment in antifouling paints. Since the phenomenon has been thoroughly described only in Atlantic species, a comparative survey of field populations from British Columbia was undertaken, and field studies were carried out to assess the relative value as bioindicators of species in the genus Nucella fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
1

Year Published

1992
1992
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(35 citation statements)
references
References 12 publications
1
33
1
Order By: Relevance
“…imposex stage 4) females. TBT-induced sterilization is not only reported for O. erinacea (Gibbs et al, 1990; this study), but occurs also in N. lapillus (Gibbs et al, 1987;Oehlmann et al, 1991), Nucella lima (Short et al, 1989), Nucella lamellosa (Bright & Ellis, 1990), Thais haemastoma (Spence et al, 1990), Urosalpinx cinerea (Gibbs et al, 1991) and Ocinebrina aciculata (in prep.). The sterilization effect of advanced imposex is different in the muricids.…”
Section: Discussionsupporting
confidence: 51%
“…imposex stage 4) females. TBT-induced sterilization is not only reported for O. erinacea (Gibbs et al, 1990; this study), but occurs also in N. lapillus (Gibbs et al, 1987;Oehlmann et al, 1991), Nucella lima (Short et al, 1989), Nucella lamellosa (Bright & Ellis, 1990), Thais haemastoma (Spence et al, 1990), Urosalpinx cinerea (Gibbs et al, 1991) and Ocinebrina aciculata (in prep.). The sterilization effect of advanced imposex is different in the muricids.…”
Section: Discussionsupporting
confidence: 51%
“…Similarly in T. gradata and Neptunea antique from Singapore (TAN, 1999;POWER and KEEGAN, 2001) a significant correlation was reported in male shell length and penis length, whereas there was no significant correlation between female shell length and penis length. In T. carinifera a significant difference in male and female penis length was observed, differently from the condition observed in species of Nucella in which generally very small variation in male and female penis length was found (BRIGHT and ELLIS, 1990). TAN (1999) suggested that each species has its own penis/pseudopenis characteristics.…”
Section: Discussioncontrasting
confidence: 65%
“…Juveniles of this species were underrepresented, and many adult females retained their egg capsules due to blockage of the genital pore. Bright and Ellis (312) note that the selective loss of reproductive potential observed for N. /amellosa possibly could result in an alteration of the competitive interactions between sympatric species of Nucella (different species of Nucella often co-occur within the intertidal zone of British Columbia).…”
Section: Effects On Aquatic Life and Wildlifementioning
confidence: 99%